Effects of high-energy electron beam irradiation on the structure, composition and morphological properties of graphene nanoplatelet films - Nurul Hidayah Mohamad Nor; Nur Afira Anuar; Noor Azrina Talik; Wan Ahmad Tajuddin Wan Abdullah; Kritsada Kittimanapun; Hideki Nakajima; Narong Chanlek; Mohd Fakharul Zaman Raja Yahya; Boon, Tong Goh (Penerbit Universiti Kebangsaan Malaysia, 2023)
This work demonstrated the effects of 1.2 GeV high-energy electron beam irradiation on a few-layers of graphene (FLG) and multi-layer graphene (MLG) films grown via an in-house hot wire chemical vapour deposition (HWCVD) system. The FLG and MLG films were grown on highly doped n-type c-Si (100) substrates which were pre-treated using argon plasma (50 W) for 1 min and 10 min, respectively. The as-prepared samples were then irradiated using a 1.2 GeV high-energy electron beam with a dosage of 1.2 × 109 e- /cm2 at atmospheric and room temperature ambient conditions. The effects of the irradiation-mediated defects on the carbon lattice structure of both graphene samples were validated from the decreased sp2 C=C carbon content, and the increase in the adventitious carbon contamination C-O-C content. Raman results showed an elevation of the ID/IG ratio and blue-shift of the 2D and G band peaks for both the irradiated samples, which validated the mediated defects due to the dislocation of carbon atoms in the graphene sheets. The blue-shifted of 2D and G peaks were much more significant in the MLG than FLG which may indicate a better self-reconstructing property for the MLG atomic network, compared to the FLG. The stability of the films against high-energy electron beam irradiation was validated by their conductivity and surface topography. In conclusion, HWCVD grown graphene nanoplatelet films have high potential for graphene-based high-energy charged particle detectors.